Producing Knowledge from within: Critical Romani Studies and the Institutional Role of the European Roma Institute for Arts and Culture (ERIAC) (Critical Romani Studies, 2026)
For centuries, the production of knowledge about Romani communities has been dominated by non-Romani scholars,institutions, and power structures. This monopoly has created a distorted and racialized understanding of Romani identity, history,and culture; an understanding that has profoundly shaped European scholarship, public policy, and everyday perceptions. This articleexamines the historical trajectory and ongoing consequences of  this knowledge regime. It explores the roots of Gypsylorism, theinfluence of eugenics, the role of ethnographic bias, and the persistent structures of antigypsyism that shape how Roma are represented in academia and society. Then the article analyses the emergence of Critical Romani Studies as an intellectual response to these structures, emphasising Romani positionality and the development of Romani epistemologies as crucial interventions. It further explores the creation and role of the European Roma Institute for Arts and Culture (ERIAC) as a transnational institutional space designed to support Romani cultural and intellectual agency. ERIAC’s priorities in knowledge production, such as the development of educational platforms, critical bibliographies, and projects on resistance, are examined as examples of how Roma-led institutions can contribute to epistemic justice, historical reparation, and the transformation of academic canons. Finally, the article reflects on future directions for Roma-led research, arguing that reclaiming knowledge production is not merely an academic endeavour but a political and cultural act. By asserting Romani epistemologies and institutional presence, Critical Romani Studies challenges centuries-old hierarchies of representation and opens pathways for new, plural, and equitable forms of understanding. The article is based on an intellectual dialogue between the authors that took place on 19 September 2025.
Keywords: Antigypsyism; Critical Romani Studies; Knowledge production; Romani positionality; Gypsylorism; European Roma Institute for Arts and Culture